SUBSTITUTION OF FISH MEAL DOSES BY USING SHRIMP HEAD FLOUR ON TILAPIA FEED (Oreochromis niloticus) - Nastiti, Ninda; Nurliah, Nurliah; Setyono, Bagus Dwi Hari (Jurnal Perikanan Unram, 2020)
This study aims to determine the effect of the use of shrimp head flour as a substitution material for fish meal doses on tilapia feed (Oreochromis niloticus) and to determine the optimal dose of shrimp head meal for the growth of tilapia. This research was conducted on December 16 to February 8 with a maintenance period of 45 days at the Laboratory of Aquaculture Study Program, Faculty of Agriculture, University of Mataram. This study used an experimental method with Completely Randomized Design (CRD) with 4 treatments and 5 replications : (control) commercial feed, (P1) 0% shrimp head flour, (P2) 20% shrimp head flour, and (P3) 35 % shrimp head flour. Calculation data were analyzed using ANOVA with a confidence level of 95%. The calculation results show that different types of feed do not significantly influence the absolute growth rate, specific growth rate, feed conversion ratio, survival rate, and feed efficiency in tilapia. The use of shrimp head flour in feed is able to provide growth as well as commercial and feed feed without the addition of shrimp head flour and can reduce production costs in the manufacture of feed.